Preparation method of new energy battery explosion-proof sheet with stable opening threshold

CN123018335APending Publication Date: 2026-10-30WUHAN RES INST OF MATERIALS PROTECTION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611216420.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

本发明的目的在于解决SPCC钢质防爆片因缺乏针对性表面处理导致的耐腐蚀能力差及开阀值不稳定的问题;通过工艺创新与镀层参数控制,在保证开阀值精度的前提下,实现长效防腐与车规级量产的一致性

Benefits of technology

[0021]本发明利用化学镀仿形特性,保证了刻痕区域的均匀覆盖,使批量生产时开阀值的过程能力指数CpK提高到1.67以上;并结合高磷非晶态镀层的高耐蚀特性,使防爆片的耐盐雾时间达到24h,在保证开阀精度的同时实现了高耐蚀目标,显著提升了动力电池的本质安全水平与车规级一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018335A_ABST
    Figure CN123018335A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of cylindrical power battery safety and surface treatment, and discloses a preparation method of a new energy battery explosion-proof sheet with stable opening valve value. The explosion-proof sheet comprises an SPCC cold-rolled steel base, an explosion score, a surface nickel-phosphorus alloy protective layer and a passivation layer. The phosphorus content of the nickel-phosphorus alloy protective layer is 9% to 13%, the thickness is 3 microns to 6 microns, and the thickness deviation between the score and the non-score is less than or equal to 10%. The preparation method comprises the following steps: obtaining a uniform nickel-phosphorus alloy plating layer under the condition that the base is at 85 to 90 DEG C and pH 4.5 to 5.0; and after passivation treatment of the plating layer, heat treatment is carried out at 200 DEG C to 250 DEG C. The process capability index CpK of the opening valve value during batch production is improved to more than 1.67, the salt mist resistance time reaches 24 hours, the opening valve precision is ensured, the high corrosion resistance target is achieved, and the safety level and the vehicle regulation level consistency of the power battery are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cylindrical power battery safety and surface treatment technology, and more specifically to a method for preparing an explosion-proof sheet for a new energy battery with a stable opening threshold. Background Technology

[0002] The explosion-proof plate of the power battery is a key safety pressure relief component on the top cover of the battery. When the pressure inside the battery rises abnormally due to thermal runaway, it can be directionally burst at the groove to release the pressure and prevent the battery from exploding.

[0003] SPCC cold-rolled steel is a common substrate for explosion-proof sheets, but it has poor corrosion resistance, especially in electrolyte environments containing fluoride ions, where it is prone to corrosion and poses safety hazards. Therefore, surface protection treatment is required.

[0004] While some existing technologies suggest using processes such as vacuum plating, electroplating, or spraying, they still have many shortcomings in practical applications. For example, traditional electroplating of nickel is limited by the characteristics of electric field distribution, resulting in severe electric field shielding at the root of micro-scratches. This leads to a thinner plating layer or even complete plating omissions at that location. Not only is the corrosion resistance insufficient, but the uneven thickness distribution at the scratches also causes fluctuations in the batch opening threshold and poor consistency, making it difficult to meet the stringent requirements of automotive-grade explosion-proof sheets for a process capability index CpK > 1.67.

[0005] Therefore, there is an urgent need for a new explosion-proof sheet treatment process specifically developed for SPCC steel substrates, which is simple in process and can ensure uniform coverage of the grooves. This process can achieve high corrosion resistance while strictly ensuring valve opening accuracy and batch consistency, thus providing a guarantee for battery safety. Summary of the Invention

[0006] In view of this, the present invention provides a method for preparing a new energy battery explosion-proof sheet with a stable opening threshold. The purpose of the present invention is to solve the problems of poor corrosion resistance and unstable opening threshold caused by the lack of targeted surface treatment in SPCC steel explosion-proof sheets; through process innovation and coating parameter control, long-term corrosion protection and consistency with automotive-grade mass production are achieved while ensuring the accuracy of the opening threshold.

[0007] One objective of this invention is to provide a new energy battery explosion-proof sheet with a stable opening threshold, comprising: an explosion-proof sheet substrate made of SPCC cold-rolled steel with directional pressure relief burst marks, and a protective layer prepared on the surface of the explosion-proof sheet substrate by chemical plating and passivation processes. The protective layer includes a nickel-phosphorus alloy plating layer and a passivation layer on its surface. The thickness of the nickel-phosphorus alloy plating layer is 3μm to 6μm, and the relative deviation between the plating thickness in the burst mark area and the plating thickness in the non-mark area is no more than 10%.

[0008] Preferably, the thickness of the explosion-proof sheet substrate is 0.3mm to 0.8mm, the explosion-proof notch is annular, and the notch depth is 50% to 80% of the thickness of the explosion-proof sheet substrate.

[0009] Further preferably, the thickness of the explosion-proof sheet substrate is 0.5 mm, and the depth of the groove is 70% of the substrate thickness.

[0010] Preferably, the phosphorus element in the nickel-phosphorus alloy coating has a mass percentage of 9% to 13% and exhibits an amorphous structure.

[0011] Preferably, the explosion-proof discs from the same production batch have a valve opening value range of no more than 0.30 MPa and a process capability index CpK > 1.67, ensuring the consistency of valve opening of the explosion-proof discs under long-term service conditions.

[0012] The second objective of this invention is to provide a method for preparing an explosion-proof sheet, comprising the following steps:

[0013] S1. Pretreatment: The SPCC steel explosion-proof sheet substrate is degreased and activated sequentially to obtain a clean and catalytically active surface, and then transferred to the plating solution in working condition within 30 seconds. S2. Chemical plating: Immerse the treated substrate in the chemical plating solution, control the plating temperature at 85℃~90℃, the pH value at 4.5~5.0, and the time at 20~40min. Through autocatalytic reaction, a uniform nickel-phosphorus alloy coating with a phosphorus content of 9%~13% and a thickness of 3μm~6μm is deposited on the substrate (including the root of the scratch) and then cleaned. S3. Post-treatment: Passivate the coating surface with passivation solution and clean it thoroughly. S4. Heat treatment: The post-treated explosion-proof sheet is heat-treated at 200℃~250℃ for 1~2 hours to eliminate residual stress in the coating and reduce hydrogen embrittlement, thus obtaining the finished explosion-proof sheet.

[0014] After heat treatment at 200℃~250℃, the bonding strength between the nickel-phosphorus alloy protective layer and the SPCC substrate reaches grade 0 of GB / T9286 cross-cut test, and the substrate shows no red rust after 24 hours of neutral salt spray test.

[0015] Preferably, in step S1, the degreasing includes one or more of organic solvent degreasing, chemical degreasing, ultrasonic degreasing, and electrolytic degreasing.

[0016] Preferably, in step S1, the activation is a process of immersing the patient in a 10% to 50% (by volume) dilute hydrochloric acid or dilute sulfuric acid solution at room temperature for 0.5 to 3 minutes.

[0017] Preferably, in step S2, the plating solution contains nickel sulfate as the main salt, sodium hypophosphite as a reducing agent, a complexing agent, a pH buffer, a stress reliever, and a stabilizer.

[0018] Preferably, the electroless plating solution contains 20 g / L to 30 g / L nickel sulfate, 25 g / L to 35 g / L sodium hypophosphite, 15 g / L to 20 g / L complexing agent, 10 g / L to 20 g / L pH buffer, 5 g / L to 10 g / L stress reliever, and 1 mg / L to 20 mg / L stabilizer.

[0019] Preferably, the complexing agent is one or more of lactic acid, malic acid, citric acid, and succinic acid; The buffer is one or more of acetic acid, sodium acetate, and ammonia water; The stress reliever is one or more of sodium saccharin, bisbenzenesulfonamide, and sodium allyl sulfonate. The stabilizer is one or more of potassium iodate, potassium iodide, and thiourea.

[0020] Preferably, in step S3, the passivation is chromium-free passivation. The chromium-free passivating agent consists of 10–20 g / L sodium hydroxide, 30–50 g / L molybdate, 0.5–1.0 g / L fluorosilicate, and 10–20 g / L pH buffer. The pH buffer can be selected from sodium acetate. The passivation process is as follows: temperature 40–60 °C, time 3–10 min.

[0021] This invention utilizes the conformal properties of chemical plating to ensure uniform coverage of the etched area, thereby increasing the process capability index CpK of the valve opening value to over 1.67 during mass production. Combined with the high corrosion resistance of the high-phosphorus amorphous coating, the salt spray resistance time of the explosion-proof sheet reaches 24 hours. While ensuring valve opening accuracy, it achieves the goal of high corrosion resistance, significantly improving the intrinsic safety level of the power battery and its consistency with automotive-grade standards.

[0022] As can be seen from the above technical solution, compared with the prior art, the present invention provides a preparation process for an explosion-proof sheet with a stable opening threshold for new energy batteries using SPCC steel substrate. Unlike existing broad surface treatment methods, the present invention utilizes the self-catalytic conformal characteristics of chemical plating to overcome the electric field shielding defects at micro-scratches in traditional electroplating, structurally ensuring uniform protection of the explosion-proof sheet. Simultaneously, by selecting stress-relieving agents and adjusting the ratio of nickel salts and reducing agents, a low-stress, high-phosphorus amorphous coating is obtained. Combined with passivation and heat treatment processes, the explosion-proof sheet achieves a salt spray resistance time of more than 24 hours without red rust and a stable opening threshold. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0024] Figure 1 The explosion-proof sheet provided in Embodiment 1 of the present invention. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Example 1 1. Substrate Preparation SPCC cold-rolled steel sheet with a thickness of 0.5mm is selected and stamped into a new energy battery explosion-proof sheet blank with a diameter of 46mm. The circular explosion marks are processed by laser processing, with a mark depth of 0.35mm (about 70% of the base thickness). The designed rated opening value is 2.00 MPa ± 0.30 MPa.

[0027] 2. Preparation process S1. Pretreatment: The explosion-proof sheet blank is ultrasonically cleaned in an alkaline degreasing solution at 60℃ for 5 minutes, and then placed in an electrolytic degreasing solution at 60℃ as the anode at a current density of 3A / dm³. 2 Electrolyze for 2 minutes under the specified conditions, then rinse with running water; subsequently immerse in 30% dilute hydrochloric acid at room temperature for 1 minute to remove oxide scale and rust, rinse quickly with running pure water, and then quickly transfer to the chemical plating solution.

[0028] S2. Chemical plating: The following plating solution formula is used: Nickel sulfate 25g / L Sodium hypophosphite 30g / L Lactic acid 18g / L Acetic acid 15g / L Sodium saccharin 10mg / L Thiourea 2 mg / L Adjust the pH of the plating solution to 4.8 with ammonia, heat in a water bath to 88°C, and load a plating volume of 1.0 dm³. 2 / L, apply plating for 25 minutes. After removal, rinse with pure water.

[0029] S3. Passivation: Immerse the plated explosion-proof sheet in a chromium-free passivation solution. The passivation solution has the following composition: Sodium hydroxide 10 g / L Sodium molybdate 40 g / L Sodium fluorosilicate 0.5 g / L Sodium acetate 10 g / L.

[0030] The processing procedure is as follows: temperature 50 ℃, time 5 min. After being removed, it is rinsed with pure water and dried.

[0031] S4. Heat treatment: Place the explosion-proof sheet in an oven at 220℃ and keep it warm for 2 hours to obtain the finished explosion-proof sheet.

[0032] 3. Performance Testing and Data Analysis (1) Coating parameters: The coating cross section was observed using field emission scanning electron microscopy. The coating thickness on the outer surface was measured to be 4.8 μm, the thickness at the bottom of the burst mark was 4.6 μm, and the relative deviation was 4.2%. The phosphorus content in the coating was measured to be 10.8% by energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) showed typical amorphous diffuse scattering peaks.

[0033] (2) Adhesion and corrosion resistance: According to GB / T 9286, the coating did not peel off (level 0); according to GB / T10125, the surface did not have red rust after 36h and corrosion appeared after 48h, which meets the design requirement of more than 24h.

[0034] (3) Valve opening stability: 50 explosion-proof disc samples were randomly selected and the valve opening value was measured. The maximum valve opening value was 2.12 MPa and the minimum valve opening value was 1.91 MPa, which met the requirements.

[0035] (4) CpK Calculation: Statistical analysis of the above 50 samples showed that the average opening value was 2.01 MPa and the standard deviation was 0.0528 MPa. The specification limits USL=2.30 MPa and LSL=1.70 MPa. The calculated process capability index CpK=1.83>1.67 indicates that the process has extremely high automotive-grade mass production consistency.

[0036] Example 2 1. Plating process This embodiment aims to verify the feasibility of the upper limit of phosphorus content. The basic steps are the same as in Embodiment 1, only the chemical plating solution formula and plating time are adjusted.

[0037] Electroless plating uses a plating solution composed of a low-concentration main salt and a high-concentration reducing agent. Nickel sulfate 20g / L Sodium hypophosphite 35g / L, Lactic acid 18g / L Acetic acid 15g / L Sodium saccharin 10mg / L Thiourea 2 mg / L The plating time is determined based on the plating rate and controlled according to the plating thickness of 4.5 to 5.0 μm.

[0038] 2 Performance Testing (1) Coating parameters: The coating cross-section was observed using a field emission scanning electron microscope. The coating thickness on the outer surface was measured to be 4.7 μm, and the thickness at the bottom of the burst mark was 4.5 μm, with a relative deviation of 4.3%. Energy dispersive spectroscopy (EDS) analysis showed that the phosphorus content in the coating was 12.7%, which was significantly higher than that in Example 1. X-ray diffraction (XRD) showed typical amorphous diffuse scattering peaks. The requirements are met.

[0039] (2) Adhesion and corrosion resistance: According to GB / T 9286, the coating did not peel off (level 0); according to GB / T10125, the surface did not have red rust after 48h, which meets the design requirement of more than 24h.

[0040] (3) Valve opening stability: 50 explosion-proof sheet samples were randomly selected to measure the valve opening value. The maximum valve opening value was 2.11 MPa and the minimum valve opening value was 1.88 MPa, which met the requirements.

[0041] (4) CpK calculation: Statistical analysis of the above 50 samples showed that the average opening value was 1.99 MPa and the standard deviation was 0.0541 MPa. The specification limits USL=2.30 MPa and LSL=1.70 MPa. The calculated process capability index CpK=1.79>1.67, which meets the requirements for automotive-grade mass production.

[0042] 3 Results Analysis Compared with Example 1, Example 2 increased the phosphorus content in the coating by adjusting the ratio of nickel to sodium hypophosphite, which significantly improved the corrosion resistance of the coating. The CpK decreased slightly, but still met the usage requirements.

[0043] Example 3 1. Plating process This embodiment aims to verify the feasibility of the lower limit of coating thickness. The basic steps are the same as in Embodiment 1, except that the coating time is reduced to 20 minutes. All other conditions remain unchanged.

[0044] 2 Performance Testing and Data Analysis (1) Coating parameters: The coating cross-section was observed using a field emission scanning electron microscope. The coating thickness on the outer surface was measured to be 3.8 μm, and the thickness at the bottom of the burst mark was 3.6 μm, with a relative deviation of 5.3%. Energy dispersive spectroscopy (EDS) analysis showed that the phosphorus content in the coating was 11.0%. X-ray diffraction (XRD) showed typical amorphous diffuse scattering peaks. The requirements are met.

[0045] (2) Adhesion and corrosion resistance: According to GB / T 9286, the coating did not peel off (level 0); according to GB / T10125, the neutral salt spray test showed no red rust on the surface after 24 hours and red rust appeared after 36 hours, which met the design requirements.

[0046] (3) Valve opening stability: 50 explosion-proof sheet samples were randomly selected to measure the valve opening value. The maximum valve opening value was 2.08 MPa and the minimum valve opening value was 1.88 MPa, which met the requirements.

[0047] (4) CpK calculation: Statistical analysis of the above 50 samples showed that the average opening value was 1.98 MPa and the standard deviation was 0.0551 MPa. The specification limits USL=2.30 MPa and LSL=1.70 MPa. The calculated process capability index CpK=1.69>1.67, which meets the automotive grade requirements.

[0048] 3 Results Analysis Compared with Example 1, the coating thickness prepared in this example is lower, resulting in slightly poorer corrosion resistance and a lower opening threshold, leading to a decrease in CpK. However, all performance characteristics meet the requirements.

[0049] Comparative Example 1 1. Plating process The same explosion-proof substrate as in Example 1 was selected, and the same pretreatment was performed. A conventional Watt-type electroplating solution (nickel sulfate 250 g / L, nickel chloride 45 g / L, boric acid 40 g / L) was used at 55°C, pH=4.5, and a current density of 3 A / dm³. 2 Under the specified conditions, nickel electroplating was performed, with the average plating thickness controlled at 4.5–5.0 μm. After plating, the same passivation and heat treatment were performed.

[0050] 2 Performance Testing (1) Coating parameters: The coating cross section was observed using a field emission scanning electron microscope. The coating thickness on the outer surface was measured to be 4.8 μm, and the thickness at the bottom of the burst mark was 2.2 μm. The relative deviation exceeded 50%, and uniform coverage could not be achieved.

[0051] (2) Adhesion and corrosion resistance: According to GB / T 9286, the coating did not peel off (level 0); according to GB / T10125, the red rust appeared at the scratched area after 24 hours, indicating insufficient corrosion resistance.

[0052] (3) Valve opening stability: 50 electroplated explosion-proof sheets from the same batch were sampled and tested for valve opening value. The measured range was a maximum valve opening value of 2.02 MPa and a minimum valve opening value of 1.78 MPa. The valve opening value fluctuated significantly and showed a significant difference in stability.

[0053] The stability was poor, with a mean strength of 1.59 MPa and a standard deviation as high as 0.41 MPa. (4) CpK Calculation: Statistical analysis was performed on the above 50 samples. The average opening value was 1.90 MPa, and the standard deviation was 0.0591 MPa. The specification limits were USL = 2.30 MPa and LSL = 1.70 MPa. The calculated process capability index CpK was 1.13 < 1.67, which did not meet the requirements.

[0054] 3 Results Analysis Compared with electroless nickel plating, electroplated nickel has poor uniform plating ability, resulting in a lower plating thickness at the scratches, which leads to insufficient corrosion resistance at the scratches and a lower opening threshold, thus failing to meet the requirements.

[0055] Comparative Example 2 1. Plating process The same substrate, plating and heat treatment process as in Example 1 were used, but no passivation treatment was performed.

[0056] 2 Performance Testing (1) Coating parameters: The coating cross section was observed using field emission scanning electron microscopy. The coating thickness on the outer surface was measured to be 4.8 μm, the thickness at the bottom of the burst mark was 4.7 μm, and the relative deviation was 2.1%. The phosphorus content in the coating was measured to be 10.9% by energy dispersive spectroscopy (EDS). X-ray diffraction (XRD) showed typical amorphous diffuse scattering peaks.

[0057] (2) Adhesion and corrosion resistance: According to GB / T 9286, the coating did not peel off (level 0); according to GB / T10125, the surface showed red rust after 24 hours of neutral salt spray test, which did not meet the design requirements.

[0058] (3) Valve opening stability: 50 explosion-proof sheet samples were randomly selected to measure the valve opening value. The maximum valve opening value was 2.11 MPa and the minimum valve opening value was 1.90 MPa, which met the requirements.

[0059] (4) CpK Calculation: Statistical analysis was performed on the above 50 samples. The mean value of the opening valve was 2.00 MPa and the standard deviation was 0.0538 MPa. The specification limits USL=2.30 MPa and LSL=1.70 MPa. The calculated process capability index CpK=1.86>1.67, which meets the automotive grade requirements.

[0060] 3 Results Analysis Compared to Example 1, the lack of passivation treatment in Comparative Example 2 resulted in a decrease in the corrosion resistance of the coating. This is because passivation treatment allows a dense oxide film to grow / deposit in situ on the surface of the electroless nickel-phosphorus coating, effectively filling and sealing the micropores of the coating and blocking the penetration channels of corrosive media into the substrate and the root of the scratch. At the same time, this composite interface layer can also suppress local pitting corrosion caused by the micro-cell effect during service, thereby significantly improving the corrosion resistance of the explosion-proof sheet throughout its entire life cycle while ensuring the scratch burst sensitivity.

[0061] This invention provides a manufacturing process for an explosion-proof sheet made of SPCC steel substrate for new energy batteries with a stable opening threshold. Unlike existing broad surface treatment methods, this invention utilizes the self-catalytic contour deposition characteristics of chemical plating to overcome the electric field shielding defects present at the root of micro-scratches in traditional electroplating. This ensures that the coating thickness deviation between the scratched and non-scratched areas is controlled within 10%, guaranteeing uniform protection of the explosion-proof sheet from a structural design perspective and laying the foundation for high consistency in the opening threshold. Simultaneously, by optimizing the ratio of main salt to reducing agent in the plating solution, a low-stress, high-phosphorus amorphous alloy coating is obtained. Passivation and heat treatment processes effectively fill micropores and eliminate residual stress, simultaneously improving the corrosion resistance and structural stability of the explosion-proof sheet.

[0062] Tests show that the explosion-proof sheet produced using the process of this invention maintains a stable process capability index (CpK) of over 1.67 during mass production, with a maximum difference in opening threshold value within the same batch of sheets of no more than 0.30 MPa. This effectively solves industry problems such as the dispersion of opening threshold value and insufficient corrosion resistance during service life caused by uneven coating in steel explosion-proof sheets. This technical solution features a simple process and controllable parameters, providing a quantifiable and highly reliable dedicated surface treatment standard for low-cost SPCC material explosion-proof sheets in the new energy battery field. It possesses significant automotive-grade mass production value and promising prospects for industrial promotion.

[0063] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0064] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A new energy battery explosion-proof sheet with a stable opening threshold, characterized in that, include: The SPCC cold-rolled steel explosion-proof disc substrate has explosion-proof grooves for directional pressure relief, and a protective layer is provided on the surface of the explosion-proof disc substrate; wherein... The protective layer includes a nickel-phosphorus alloy plating layer and a passivation layer on its surface. The thickness of the nickel-phosphorus alloy plating layer is 3μm to 6μm, and the relative deviation between the plating thickness in the explosion-marked area and the plating thickness in the non-marked area is no more than 10%.

2. The explosion-proof sheet for a new energy battery with a stable opening threshold as described in claim 1, characterized in that, The thickness of the explosion-proof sheet substrate is 0.3mm to 0.8mm, and the explosion-proof notch is annular with a notch depth of 50% to 80% of the thickness of the explosion-proof sheet substrate.

3. The explosion-proof sheet for a new energy battery with a stable opening threshold according to claim 1, characterized in that, The phosphorus element in the nickel-phosphorus alloy coating is 9% to 13% by mass and has an amorphous structure.

4. The explosion-proof sheet for a new energy battery with a stable opening threshold according to claim 1, characterized in that, For the same production batch of the explosion-proof disc, the range of the opening valve value is no greater than 0.30 MPa, and the process capability index CpK > 1.

67.

5. The method for preparing the explosion-proof sheet for new energy batteries according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Pretreatment: SPCC cold-rolled steel sheet is made into a substrate with explosion marks, and the SPCC steel explosion-proof sheet substrate is subjected to degreasing and activation treatment in sequence. S2. Chemical plating: The treated substrate is immersed in a chemical plating solution, and the plating temperature is controlled at 85℃~90℃, the pH value is 4.5~5.0, and the time is 20~40min, to deposit a nickel-phosphorus alloy coating on the surface of the substrate. S3. Post-treatment: After plating is completed and the surface is cleaned, passivation solution is used to passivate the plating surface. S4. Heat treatment: The post-processed explosion-proof sheet is heat-treated at 200℃~250℃ for 1~2 hours to obtain the finished explosion-proof sheet.

6. The preparation method according to claim 5, characterized in that, In step S2, the plating solution contains nickel sulfate as the main salt, sodium hypophosphite as the reducing agent, a complexing agent, a pH buffer, a stress reliever, and a stabilizer.

7. The preparation method according to claim 6, characterized in that, The electroless plating solution contains 20 g / L to 30 g / L nickel sulfate, 25 g / L to 35 g / L sodium hypophosphite, 15 g / L to 20 g / L complexing agent, 10 g / L to 20 g / L pH buffer, 5 g / L to 10 g / L stress reliever, and 1 mg / L to 20 mg / L stabilizer.

8. The preparation method according to claim 6 or 7, characterized in that, The complexing agent is one or more of lactic acid, malic acid, citric acid, and succinic acid; The buffer is one or more of acetic acid, sodium acetate, and ammonia water; The stress reliever is one or more of sodium saccharin, bisbenzenesulfonamide, and sodium allyl sulfonate. The stabilizer is one or more of potassium iodate, potassium iodide, and thiourea.

9. The preparation method according to claim 5, characterized in that, In step S3, the passivation is chromium-free passivation, and the chromium-free passivating agent is composed of 10-20 g / L sodium hydroxide, 30-50 g / L molybdate, 0.5-1.0 g / L fluorosilicate and 10-20 g / L pH buffer.

10. The preparation method according to claim 5, characterized in that, In step S3, the passivation treatment specifically involves a temperature of 40–60 °C and a time of 3–10 min.